A Scaffold‐based Deep Generative Model Considering Molecular Stereochemical Information. Issue 12 (6th October 2022) - Xu, Tianxu; Wang, Minjun; Liu, Xiaoqian; Feng, Dawei; Zhu, Yanjuan; Fan, Zhe; Rao, Shurong; Lu, Jing
Abstract: Designing molecules with specific scaffolds can facilitate the discovery and optimization of lead compounds. Some scaffold‐based molecular generation models have been developed using deep‐learning methods based on specific scaffolds, although incorporating scaffold generalization is expected to achieve scaffold hopping. Moreover, most of the existing models focus on the 2D shape of the scaffold and overlook the stereochemical properties of the compound, especially for natural products. In this study, we optimized the scaffold‐based molecular generation model designed by Lim et al . ( Chemical Science 2020, 11, 1153–1164). Real‐time ultrafast shape recognition with pharmacophore constraints (USRCAT) was introduced into the model to search for molecules similar to the 3D conformation and pharmacophore of the input scaffold sourced from the training set; the searched molecules were then used as new scaffolds to execute scaffold hopping. The optimized model could generate new molecules with the same chirality as the input scaffold. Furthermore, the probability distribution of the molecular structure and various physicochemical properties were analyzed to evaluate the model's generation capability. We thus believe that the optimized model can provide a basis for medicinal chemists to explore a wider chemical space toward optimization of the lead compounds and to screen the virtual compound library. Abstract :